Dermatoscopic Patterns in Childhood Vitiligo and Their Association With Reflectance Confocal Microscopy Findings - Juan Alberto Godínez-Chaparro; Rodrigo Roldán-Marín; Adrián Soto-Mota; Claudia Camelia Calzada-Mendoza (Mattioli1885, 2023)
Introduction: The diagnosis of vitiligo is mainly based on clinical findings. However, dermoscopy or reflectance confocal microscopy (RCM) could be useful for assessing its progression (stability, pigmentation, or depigmentation). Objective: To evaluate the correlation of dermatological findings by dermoscopy and RCM in pediatric vitiligo. Methods: We conducted a cross-sectional, descriptive, and analytical clinical study. Pediatric patients with vitiligo of both sexes, aged >1 year and <18 years, with all spectrums of the disease were included. Vitiligo lesions were evaluated clinically, by dermoscopy, and microscopy. Results: A total of 40 patients with vitiligo were included. Eight dermoscopic patterns were found: reduced/absent pigment network, perifollicular pigmentation, trichromic, tapioca sago, perifollicular depigmentation, starburst, leukotrichia, and erythema. Skin with a normal pigment network showed complete dermal papillary rings and half-rings. Skin with reduced/absent pigment network had an absence of papillary rings or only showed half-rings and was more common in unstable vitiligo. The trichrome pattern only showed half-rings. The tapioca sago pattern showed complete papillary rings and appeared in younger patients. Perifollicular pigmentation showed half-rings and complete rings and did not show associations. The diffuse borders did not present complete papillary structures. We found that vitiligo duration time of <24 months (OR 4.56 CI 1.09-18.99) and absent papillary rings (OR 2.75 CI 1.01-7.51) are associated with an unstable prognosis. Conclusions: The dermoscopic and microscopic findings, such as the reduction/absence of the pigment network, tapioca sago pattern, and absence of papillary rings, can be used to support the evaluation of the clinical prognosis of vitiligo.